Safety of 6000 intravitreal dexamethasone implants. Issue 1 (30th April 2019) - Rajesh, Bindu; Zarranz-Ventura, Javier; Fung, Adrian T; Busch, Catharina; Sahoo, Niroj Kumar; Rodriguez-Valdes, Patricio J; Sarao, Valentina; Mishra, Sanjay Kumar; Saatci, A Osman; Udaondo Mirete, Patricia; Querques, Giuseppe; Farah, Michel Eid; et al.
Abstract : Purpose: To evaluate the real-life safety profile of intravitreal dexamethasone implant injection for various retinal conditions. Methods: Retrospective multicenter analysis of intravitreal dexamethasone implant injections (700 µg) due to various retinal conditions including central retinal venous occlusion (1861 injections), diabetic macular oedema (3104 injections), post-surgical cystoid macular oedema (305 injections) and uveitis (381 injections). The eyes were evaluated mainly for the occurrence of adverse events such as glaucoma, cataract, retinal detachment and endophthalmitis along during the follow-up period. Results: A total of 6015 injections in 2736 eyes of 1441 patients (mean age of 65.7±12.9 years) were in total analysed over an average period of 18 months (range 6 months to 102 months). A total of 576 eyes (32.5% of the phakic eyes) developed cataract requiring surgical intervention. However, visually insignificant cataract progression was observed in another 259 phakic eyes (14.6%) which did not require surgical removal. A total of 727 eyes (26.5%) experienced an intraocular pressure (IOP) rise of >25 mm Hg, with 155 eyes (5.67%) having a prior history of glaucoma and 572 eyes (20.9%) having new onset IOP rise. Overall, more than 90% of eyes with IOP rise were managed medically, and 0.5% eyes required filtering surgery. Endophthalmitis (0.07%), retinal detachment (0.03%) and vitreous haemorrhage (0.03%) were rare. There was no significant change in visual acuity (p=0.87) and central macular thickness (p=0.12) at the last follow-up. Conclusion: This is the largest real-life study assessing the safety of intravitreal dexamethasone implant injections in various retinal conditions. Cataract progression and intraocular pressure rise are the most common side effects, but are often rather easily manageable.